Environmental issues, policies and media reporting in Nepal / Tirtha Koirala - Koirala, Tirtha (Faculty of Communication and Media Studies (FCMS), 1993)
There is no one issue form where discussion about Nepal's environment and development problems can be started. Talking economics, the per capita GNP is about US $ 160 which makes it one of the poorest countries in the world. On the environmental front too, the problems are no less severe. Deforestation is one of the major environmental problems facing Nepal. Over 75 percent of the county's 18 million people depend on firewood as the main source of energy. Animal husbandry which is also a part of the lives of most of the Nepalis-more then 90 per cent of whom are dependent on agriculture to make a living-also adds to the pressure on the forests.